2010
DOI: 10.1577/t09-140.1
|View full text |Cite
|
Sign up to set email alerts
|

Striped Bass Habitat Selection Rules in Reservoirs without Suitable Summer Habitat Offer Insight into Consequences for Growth

Abstract: The traditional view of habitat requirements for inland striped bass Morone saxatilis suggests that these fish need dissolved oxygen (DO) levels above 2–3 mg/L and temperatures below 25°C to thrive. However, striped bass are found in reservoirs where hypolimnetic hypoxia forces them into warm temperatures (27–30°C) for much of the summer, and contrary to expectations, these populations do not consistently experience poor growth or mortality. We used telemetry of adult striped bass in Badin Lake, North Carolina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
(73 reference statements)
1
13
0
Order By: Relevance
“…When prey availability was inadequate, growth of white crappies during periods of high temperatures was reduced, and white crappies lost weight in some cases. Similar abilities to offset metabolic costs of high water temperatures by feeding heavily on abundant warmwater prey fish were recently demonstrated for striped bass (Thompson et al 2010).…”
Section: Discussionsupporting
confidence: 67%
“…When prey availability was inadequate, growth of white crappies during periods of high temperatures was reduced, and white crappies lost weight in some cases. Similar abilities to offset metabolic costs of high water temperatures by feeding heavily on abundant warmwater prey fish were recently demonstrated for striped bass (Thompson et al 2010).…”
Section: Discussionsupporting
confidence: 67%
“…Costantini et al (2008) examined the impact of hypoxia on 2-year-old and older Striped Bass in Chesapeake Bay through bioenergetics modeling and concluded that a temperature-oxygen squeeze (mismatch of water column regions of desirable temperature and dissolved oxygen; Coutant 1985;Price et al 1985;Coutant 2013) had not limited the growth potential of Striped Bass. Adequate levels of Striped Bass prey offset the negative effects of warm temperatures and suboptimal dissolved oxygen in reservoirs (Thompson et al 2010). Weights at age of 7-to 10-year-old Striped Bass along the Atlantic coast were significantly and positively associated with D t /P t estimates from the S-H model, and these ages represented larger fish likely to migrate along the Atlantic coast rather than reside in Chesapeake Bay in summer (Dorazio et al 1994;Secor and Piccoli 2007).…”
Section: Atlantic Menhaden and Striped Bass Linkagementioning
confidence: 99%
“…Striped Bass in Lake Martin were found to undergo a "habitat squeeze" during summer as they became trapped in limited thermal refugia between warm, oxygenated, epilimnetic waters and cool, anoxic or hypoxic, hypolimnetic waters, which is a common phenomenon in other systems (Coutant 1985;Matthews et al 1985). The general behavior pattern of Striped Bass in Lake Martin was to select cooler temperatures if DOC was above 3.2 mg/L, but below that level, fish would generally select for warmer temperatures, similar to what Thompson et al (2010) described for Striped Bass in a shallow, eutrophic reservoir in…”
Section: Discussionmentioning
confidence: 65%
“…Some Striped Bass moved above the thermocline in September, where they existed in water temperatures warmer than 25 • C and DOC greater than 4 mg/L. This apparent individualistic behavior has been described for other fish species (Sammons and Maceina 2005), and it appears that Striped Bass in Lake Martin likewise employ various strategies to cope with changing water quality variables during the summer (Thompson et al 2010). Striped Bass have been found to use springs or hypolimnetic discharges for summer refugia if ambient conditions during summer are unfavorable (Cheek et al 1985;Moss 1985;Braschler et al 1989;Van Den Avyle and Evans 1990;Wilkerson and Fisher 1997).…”
Section: Environmental Variable Quality Habitat Total Habitatmentioning
confidence: 65%